Diagnostico de una comunidad rural de pequenos agricultores - Sena, M. de G.C. de (International Center for Tropical Agriculture, 1989)
The methodology, based on the principle research-action, used to understand the social reality of small-scale cassava farmers in Guapira (Bahia, Brazil) is described. Specific objectives were to identify the main problems of the community under study, available production factors, and research problems as well as select appropriate technologies. Data was collected through interviews carried out with community leaders, members of farmers' associations, and farmers, among others. Preliminary results indicate that 68 percent of the farmers own the land, 4 percent are tenants, and 26 percent are in process of legalizing their situation. Cassava is the main crop, followed by yam; of the total cassava production, 58 percent is transformed into table flour and 42 percent is consumed fresh. Starch production is low, reaching only 0.5 percent of total root production. Products are traded in the open market as well as through middlemen. Wholesaling is uncommon. (CIAT)